2011
DOI: 10.1177/147323001103900608
|View full text |Cite
|
Sign up to set email alerts
|

Large Intervening Non-Coding RNA HOTAIR is Associated with Hepatocellular Carcinoma Progression

Abstract: Increasing evidence suggests that large intervening non-coding RNAs (lincRNAs) regulate key pathways in cancer invasion and metastasis. In this observational retrospective study, the expression of the oncogenic lincRNA HOX transcript antisense RNA (HOTAIR) gene was measured in 63 patients with hepatocellular carcinoma (HCC) following hepatic resection. The HOTAIR gene was significantly overexpressed in HCC tissues compared with adjacent non-tumour tissues. Patients with high HOTAIR gene expression in their tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
310
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(322 citation statements)
references
References 37 publications
10
310
0
2
Order By: Relevance
“…LncRNAs have emerged as important regulators of gene expression, showing cell-specific expression patterns and subcellular localization and are involved in many biological roles including imprinting, epigenetic regulation, apoptosis, and cell cycle (26,27). The well-characterized lncRNA HOX transcript antisense RNA (HOTAIR) has been found to be up-regulated in multiple cancers including breast, colorectal, hepatic, gastric, and pancreatic cancers (28)(29)(30)(31)(32)(33). HOTAIR modulates chromatin structures by serving as a scaffold and recruiting histone modifiers (28).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs have emerged as important regulators of gene expression, showing cell-specific expression patterns and subcellular localization and are involved in many biological roles including imprinting, epigenetic regulation, apoptosis, and cell cycle (26,27). The well-characterized lncRNA HOX transcript antisense RNA (HOTAIR) has been found to be up-regulated in multiple cancers including breast, colorectal, hepatic, gastric, and pancreatic cancers (28)(29)(30)(31)(32)(33). HOTAIR modulates chromatin structures by serving as a scaffold and recruiting histone modifiers (28).…”
Section: Significancementioning
confidence: 99%
“…HOTAIR modulates chromatin structures by serving as a scaffold and recruiting histone modifiers (28). In breast cancer, HOTAIR promotes cancer cell invasion and metastasis in vivo through epigenetic silencing of metastasis suppressor genes (29)(30)(31)(32)(33). In patients with nonsmall cell lung cancer, high expression of the lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was associated with metastases and poor survival, indicating its importance as a prognostic biomarker (34).…”
Section: Significancementioning
confidence: 99%
“…11,16 In fact, previous studies have shown that particular deregulated lncRNAs are important regulators of tumor formation and progression. 17,24 For example, the antisense intergenic RNA HOX Antisense Intergenic RNA (HOTAIR) is highly expressed in multiple types of primary somatic tumors, such as hepatocellular carcinoma, 25,26 pancreatic cancer, 27 and gastric cancer, 28 as well as some metastatic tumors, including metastatic breast tumors 29 and melanoma. 30 Moreover, high HOTAIR level is associated with poor patient survival rate 20,27 and tumor recurrence.…”
Section: Lncrnas In Cancermentioning
confidence: 99%
“…31 Moreover, HOTAIR can also interact with the LSD1/CoREST/REST complex, which coordinates targeting of LSD1 to chromatin for coupled histone K4 demethylation. 32 Given its important role in the epigenetic regulation of gene expression by mediating the modulation of chromatin structures, it is not surprising that HOTAIR performs vital functions in increasing cancer invasiveness and metastasis 25,26,29 and shows immense clinical relevance. Particularly, lncRNA expression levels may be extremely useful for monitoring tumors, and we consider lncRNAs to be novel cancer diagnostic tools and a source of future therapies.…”
Section: Lncrnas In Cancermentioning
confidence: 99%
“…Circulating nucleic acids (CNAs), both RNA and DNA species, are extracellular nucleic acids found in cell-free serum, plasma and other body fluids from healthy subjects, as well as from patients. 87 In addition, there is evidence of a good correlation between tumor-associated changes in genomic, epigenetic or transcriptional patterns, and alterations in CNA levels, 88 strongly pointing to the utility of this blood biomarker class as promising clinical tools. Our recent studies and others have suggested that cancer-specific miRNAs are stable and detectable in the blood, sputum and urine of cancer patients.…”
Section: Lncrnas As Diagnostic and Therapeutic Toolsmentioning
confidence: 99%